Transformation of PRRSV’s Glycoprotein GP5 under Regulation of a Seed Specific Promoter into Soybean - Sen, Dao Thi; Lan, Vo Thi Thuong; Van, Nguyen Tuong; Ha, Chu Hoang (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: PRRS (Porcine reproductive and respiratory syndrome) is the most significant infectious disease currently devastating the swine industry.  Plant-based subunit vaccines offer viable, safe, and environmentally friendly alternatives to conventional vaccines. In order to diversify antigen sources for vaccine production to against PRRSV, co-expressing LTB and GP5 genes encoding  an important structure protein of PRRSV under regulation of a seed specific promoter were constructed using both conventional and Gateway methods.  The developed plant transformation vector pDest-phaso-LTB-GP5 was transferred into soybean DT26 using Agrobacterium -mediated transformation method and cotyledonary node as initial explants.  The PCR analysis verified 13 out of 56 putative transgenic plants carrying GP5 gene and transformation efficiency was equal to 2.6%.  A further study will be carried out to investigate the expression of GP5 in soybean seeds to confirm the benefit of the expression vector in the development of a subunit plant-based vaccine against PRRS.  Keywords : PRRS (Porcine reproductive and respiratory syndrome); glycoprotein GP5 gene; seed specific promoter; genetic transformation; soybean.